1981
DOI: 10.1524/ract.1981.28.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Recoil 38Cl Atoms with Liquid Chlorobenzenes

Abstract: The reactions of recoil " C1 atoms (produced in a high flux nuclear reactor) with liquid chlorobenzenes were investigated. The yields of " CI-for-H and Q-replacement reactions, of inorganic Compounds and of polymers were measured in the presence of scavengers, by GLCtechniques and by gelfiltration over Sephadex. In unscavenged chlorobenzene, C^ Hj" C1 (52%) is formed via a direct hot replacement reaction (5%), via a thermal exchange reaction (28%) and via a radiation induced exchange reaction (19%). It is beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 17 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…The total yield of the dimeric and trimeric (φ 2 + φ 2 ) compounds as measured by gelfiltration experiments (3.0-4.3%), is somewhat lower than the "missing fraction" (6.3-7.9%) as measured by GLC. We have no reasonable explanation for the differences in these yields, but it is obvious that the yield of the high boiling products is much lower than that observed for other chloroarenes, such as C 6 H s C1, C 6 H 4 C1 2 [17] and C 6 H 4 C1CH 3 [9] irradiated under similar conditions. In general, the yields of high boiling 38 CI labeled compounds formed from substituted benzenes are in the order of 20-30%, but they are lowered in the presence of I 2 or Br 2 [24].…”
Section: Polymer and Inorganic Yieldsmentioning
confidence: 59%
See 4 more Smart Citations
“…The total yield of the dimeric and trimeric (φ 2 + φ 2 ) compounds as measured by gelfiltration experiments (3.0-4.3%), is somewhat lower than the "missing fraction" (6.3-7.9%) as measured by GLC. We have no reasonable explanation for the differences in these yields, but it is obvious that the yield of the high boiling products is much lower than that observed for other chloroarenes, such as C 6 H s C1, C 6 H 4 C1 2 [17] and C 6 H 4 C1CH 3 [9] irradiated under similar conditions. In general, the yields of high boiling 38 CI labeled compounds formed from substituted benzenes are in the order of 20-30%, but they are lowered in the presence of I 2 or Br 2 [24].…”
Section: Polymer and Inorganic Yieldsmentioning
confidence: 59%
“…In the case of various substituted chlorobenzenes, only some percent of 100 Brought to you by | University of California Authenticated Download Date | 6/13/15 6:07 PM dimers were formed, and almost no higher polymers, as was found by gelfiltration experiments [9,17]. However, these results do not necessarily mean that addition of 38 C1 atoms -forming a 38 Cl-cyclohexadienylradicaldoes not take place, because it was found that for several substituted arenes (C 6 H S X, X = CI, N0 2 , CHO) the yield of monomeric species eluting from a gelfiltration column was much higher than the summed yield of the 38 Cl-for-H and X-substitution products, as determined by GLC experiments [17,20]. In the case of the 38 C1/C 6 H S C1/I 2 system, the difference in yield of monomeric compounds as determined by both methods was about 20%.…”
Section: Polymer and Inorganic Yieldsmentioning
confidence: 83%
See 3 more Smart Citations